The role of mobile characteristics on mobile money innovations - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2022)
This study focuses on linkages between bank accounts and supply-side mobile money drivers for mobile money innovations. It seeks to understand how bank accounts can be complemented with mobile subscription and mobile connectivity dynamics (i.e., mobile connectivity coverage and mobile connectivity performance) for mobile money innovations. The empirical evidence is based on quadratic Tobit regressions. First, there are positive net relationships from the roles of mobile subscriptions and mobile connectivity coverage in modulating bank accounts for mobile money innovations. Second, mobile connectivity performance does not significantly modulate bank accounts for mobile money innovations. Third, given the negative marginal relationships associated with the positive net relationships, thresholds for complementary policies in mobile money supply factors that are worthwhile for bank accounts to stimulate mobile money innovations are provided. The thresholds are: (i) mobile subscription rates of 87.50%, 80.50%, and 98.50% of the adult population for respectively, the mobile money accounts, the mobile used to send money, and the mobile used to receive money, and (ii) mobile connectivity coverages of 64.00%, 69.33%, and 78.00% for respectively, the mobile money accounts, the mobile used to send money, and the mobile used to receive money.
Keywords: D10; D14; D31; D60; O30; 330; Mobile money; technology diffusion; financial inclusion; inclusive innovation